Improving Internet access in the UMMC - A Nadi it innovation - Bulgiba, Awang; Rohani, Khairuliza; Rasiah, Raja Isaiah; Ahmad, Esmadi; Ahmad Mohktar, Norazlin; Mohd Shafie, Nor Mila; Shahrudin, Shereena; Awang, Asmarudi; Abdul Jalil, Marina; Ibrahim, Siti Noor Ismariani; Mohtar, Faradiba; Ani, Azura (Faculty of Medicine, University of Malaya, 2000)
In early 2001, Nadi IT (the IT department of the UMMC) migrated the UMMC leased line from its old 64 kbps line to the 34 Mbps University of Malaya leased line. The migration was a new learning experience for Nadi IT and many lessons were learnt along the way. This paper describes the idea behind the migration process, the reason for the migration, problems and solutions to all these problems as well as the benefits derived from the migration. The experience of this process may be useful to others wishing to improve IT facilities without resorting to expensive solutions.